PENGEMBANGAN KOMIK DIGITAL BERBASIS CONTEXTUAL TEACHING AND LEARNING PADA MATERI CAHAYA DAN ALAT OPTIK - Faisah, Nur; Fikriyah, Aida; Ahied, Mochammad; Rakhmawan, Aditya; Yasir, Mochammad (Natural Science Education Research, 2025)
The development of digital comics is based on the minimal use of digital-based learning media, the lack of interest and motivation in learning science. This study aims to determine the feasibility, readability level and student response to digital comics based on Contextual Teaching and Learning on the topic of light and optical instruments. This research is a development research using the ADDIE development model. The research was conducted at the UPTD of SMP Negeri 3 Bangkalan in the 2024/2025 academic year. The results of the development of digital comics obtained a media feasibility score of 88.44% with very feasible criteria. The feasibility of the material obtained a score of 84.20% with very feasible criteria. The media readability level obtained a score of 86.63% with very high criteria, and student responses to digital comics were 83.88% with very good criteria. Based on the results obtained, it is known that digital comics based on Contextual Teaching and Learning are suitable for use in learning the material of light and optical instruments.